AJARAN MORAL PENDAKWAH DALAM WAYANG TAUHID LAKON “BABAD SUNAN GIRI SAJIAN” KI SUNARDI WIROCARITO - Luwiyanto, Luwiyanto; Pebryawan, Krisna; Tukiyo, Tukiyo (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
Wayang tauhid is a da’wah puppet, which contains the story of the success of the struggle of the scholars or saints, especially the walisongo. Research on this type of puppet has not been done much. The material object of this research is the monotheistic puppet play “Babad Sunan Giri” presented by Ki Sunardi Wirocarito, while the formal object is moral teachings within the scope of Javanese ethics. The purpose of the research is to analyze and then explain what moral teachings are revealed in the text of the play “Babad Sunan Giri”. To what extent the moral teachings contribute to supporting the development of character education. This research is a literature research with a philosophical analysis model with several methodical steps, namely: description, analysis, interpretation, internal coherence, and reflection. The results of the study: wayang tauhid play Babad Sunan Gresik as a medium for conveying moral values for proselytizing teachers, namely sincerity, knowledge (religion) and good character. These three teachings support and shape the personal character of da’wah teachers in particular and the Indonesian nation in general.